THE EFFECT OF INVESTMENT, INTEREST RATES AND POVERTY ON ECONOMIC GROWTH IN INDONESIA - Asrian, Wahyu; Saharuddin, Saharuddin (LPPM Universitas Malikussaleh, 2024)
This study aims to analyze the effect of Investment, Interest Rates and Poverty on Economic Growth in Indonesia. The independent variables include investment, interest rates and poverty while the dependent variables include economic growth. The data used in this research is secondary data for the period 1999-2020. The regression model used in this study is the multiple linear regression model. This study uses classical assumption tests such as the normality test, heteroscedasticity test, autocorrelation test and multicollinearity test. The regression tool in this study used eviews10 software. Based on the results of the research, it shows that investment has a negative and significant effect on economic growth in Indonesia. Interest Rates have a positive and insignificant effect on economic growth in Indonesia. Poverty has a negative and significant impact on economic growth in Indonesia, while for all the variables Investment, interest rates and poverty together are not significant for economic growth. The test results for the coefficient of determination show that there is a relationship between the independent variables and the dependent variable in this study of 21.02%, which means that the other 78.97% is influenced by other variables outside of this study.